KONTRIBUSI METODE PERSEDIAAN BARANG YANG TEPAT TERHADAP KELANCARAN ARUS PEMAKAIAN SUKU-CADANG PESAWAT DI SEKOLAH TINGGI PENERBANGAN INDONESIA CURUG-TANGERANG - A. Nugroho Budi; Sihono (Politeknik Penerbangan Indonesia Curug, 2019)
Inventories is not only considered a burden because it is wasteful, but at the same time it can also be considered as wealth that can be immediately disbursed in the form of product activities. The problem is focused on the current situation for the service and management of contributions and distribution of training aircraft parts that have an impact on the smooth flight training. With the existing problems the writer tries to solve the problem, in the current condition in the warehouse. As a result, these items cannot be obtained instantly, but a grace period is needed to get or find a location, a non-systemic numbering system using a computer. With a manual system, the easiest way to do it is done. Still using the document paper form as a control tool. The limitation is even lacking in responding to the importance of the warehouse planning and management system so that training time is a bit hampered by time. In the research opportunity that we raised on the method of contributing to the smooth flow of usage of restricted aircraft parts without evaluating energy and budget, so it is expected to make a single step change in the system of goods contribution to cut the time and the right inventory.